Accumulation and Dispersion of Microplastics near A Submerged Structure: Basic Study Using A Numerical Wave Tank - Le Duc Quyen; Jun Myoung Choi (Journal of Marine Science and Engineering, 2022)
The presence of microplastics has been reported in most marine environments. Their accumulation can affect the marine ecosystem, and their consumption by small organisms of various sizes can indirectly affect human beings who consume them. Recent observations have reported the pathways and fates of microplastics surrounding man-made coastal structures, such as artificial reefs. However, basic research elucidating the physical behavior near the structure is scarce. We implemented a two-dimensional numerical wave flume simulating intermediate waves with a weak current in a coastal area to investigate the behaviors of microplastics corresponding to parameters such as particle size (0.2, 1, and 5 mm), particle density (900, 1000, and 1100 <semantics>kg/m3</semantics>), and submerged artificial structure. The results showed that smaller particles had a stronger horizontal dispersion but a weaker horizontal advection. Installing a submerged structure increased the flow rate above the structure. It also increased particle accumulation upstream and downstream near the edge and corner of the structure. The accumulation was significantly affected by the installation of the structure when the resuspension of microplastics occurred intermittently. This work elucidates the mechanisms underlying the distribution, accumulation, and dispersion of microplastics that are important in predicting the fate of microplastics in the vicinity of artificial structures.